Japanese language learning motivation through interaction with native speakers: A case study - Hưng, Nguyễn Minh; Trinh, Hồ Lê Thị Xuân (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
The research aims at investigating social-psychological orientations of HIUJLLs (Japanese Language Department learners of Hong Bang International University). A survey and a semi-structured interview are governed by 68 students ranging from 2nd to 4th academic year with various Japanese levels from elementary to advanced. Besides, SPSS (Statistical Package for the Social Sciences) is employed to analyze the collected data by percentage, mean of frequency and standard deviation. As a result, the research reveals that participants are generally motivated at a very high level in interacting with native speakers both Japanese teachers and students. Also, students affirm that their learning with native speakers if well arranged and designed would result in intense motivation and inspiration for them to learn Japanese much harder. As a result, some recommendations are made for further preparation and arrangement of comprehensively structured settings for long-term interactions with native speakers in Japanese language teaching and studying methodology.